2008
DOI: 10.1016/j.cpr.2007.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Selective attention to threat versus reward: Meta-analysis and neural-network modeling of the dot-probe task

Abstract: Two decades of research conducted to date has examined selective visual attention to threat and reward stimuli as a function of individual differences in anxiety using the dot-probe task. The present study tests a connectionist neural-network model of meta-analytic and key individual study results derived from this literature. Attentional bias for threatening and reward-related stimuli is accounted for by connectionist model implementation of the following clinical psychology and affective neuroscience princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
162
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(181 citation statements)
references
References 158 publications
(75 reference statements)
16
162
1
2
Order By: Relevance
“…Therefore, in the present study it is possible that the unpredictable context primed defense system activation, which in turn interfered with reward processing. This is consistent with previous research demonstrating that threat processing trumps reward processing (Frewen, Dozois, Joanisse, & Neufeld, 2008), and research indicating that stress can alter dopaminergic functioning (Lemos et al, 2012) and diminish both neural sensitivity to reward (Porcelli, Lewis, & Delgado, 2012) and reward learning (Bogdan & Pizzagalli, 2006). Overall, the present study suggests that a task-irrelevant unpredictable context has the capacity to alter a neural measure of reward system functioning.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, in the present study it is possible that the unpredictable context primed defense system activation, which in turn interfered with reward processing. This is consistent with previous research demonstrating that threat processing trumps reward processing (Frewen, Dozois, Joanisse, & Neufeld, 2008), and research indicating that stress can alter dopaminergic functioning (Lemos et al, 2012) and diminish both neural sensitivity to reward (Porcelli, Lewis, & Delgado, 2012) and reward learning (Bogdan & Pizzagalli, 2006). Overall, the present study suggests that a task-irrelevant unpredictable context has the capacity to alter a neural measure of reward system functioning.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, in the previous experiments, participants may have covertly shifted attention away from the negative image (e.g., to the side of the computer monitor), thereby interrupting the initial encoding of the negative images. Although this explanation may be at odds with claims that attention rapidly and reflexively shifts toward potentially negative images (Bradley et al, 1997;Eastwood, Smilek, & Merikle, 2001;Koster, Crombez, Van Damme, Verschuere, & De Houwer, 2004;Öhman et al, 2001), there is some evidence that an attentional bias toward negative images is robust only when one tests populations that have been selected for high anxiety; among nonselect and populations selected for low-anxiety, there is some evidence for a bias away from negative information (Bar-Haim, Lamy, Lee, Bakermans-Kranenburg, & van Ijzendoorn, 2007;Becker & Detweiler-Bedell, 2009;Frewen et al, 2008). Thus, it is possible that a reflexive attentional shift away from the negative images impeded their identification and storage.…”
Section: Methodsmentioning
confidence: 99%
“…If so, the poor performance with negative images may have reflected a rapid shift of resources away from the negative images toward the positive images. This shift of resources could be accounted for by an attentional bias toward positive stimuli (Frewen, Dozois, Joanisse, & Neufeld, 2008) or by a tendency to rapidly deploy resources to negative stimuli but to quickly remove them (Rinck & Becker, 2006).…”
mentioning
confidence: 99%
“…The large variability in the experimental procedure and the populations used for testing make it difficult to compare the results and conduct a reliable meta-analysis. To date, analyses indicated that the intensity of the threatening stimuli determines the magnitude of the attentional bias (Frewen, Dozois, Joanisse, & Neufeld, 2008) and that the attentional bias seems to be dependent on stimulus presentation time (Bar-Haim, Lamy, Pergamin, Bakermans-Kranenburg, & van IJzendoorn, 2007). Because many research articles had to be left out of the previous meta-analyses due to the large methodological variability in the literature, we will here provide a full review of the literature on dot-probe tasks and will discuss related methodological issues.…”
Section: The Dot-probe Taskmentioning
confidence: 99%